Association between serum Klotho levels and estimated pulse wave velocity in postmenopausal women: a cross-sectional study of NHANES 2007–2016 - Wang, Baiqiang; Xu, Wenqu; Mei, Zeyuan; Yang, Wei; Meng, Xiao; An, Guipeng (Frontiers in Endocrinology, 2024)
Backgr ound: Postmenopausal women are at an increased risk of arterial stiffness, which can be assessed using estimated pulse wave velocity (ePWV). This study aimed to investigate the relationship between serum klotho levels and ePWV in postmenopausal women.: This cross-sectional study used data from postmenopausal women who participated in the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2016. Participants were divided into two groups based on the presence of hypertension. Weighted multivariate linear regression was used to analyze the relationship between serum Klotho levels and ePWV in each group.Restricted cubic spline models with multivariable adjustments were employed to examine nonlinear associations within each group.Results: Our analysis included 4,468 postmenopausal women from the NHANES database, with 1,671 in the non-hypertensive group and 2,797 in the hypertensive group. In all regression models, serum Klotho (ln-transformed) levels were significantly and independently negatively correlated with ePWV in the non-hypertensive group. After fully adjusting for confounders, a 1-unit increase in ln(Klotho) was associated with a 0.13 m/s decrease in ePWV (β = -0.13, 95% CI -0.23 to -0.03; p = 0.008). Additionally, in the fully adjusted model, participants in the highest quartile of ln(Klotho) had an ePWV value 0.14 m/s lower than those in the lowest quartile (p for trend = 0.017; 95% CI -0.23 to -0.05; p = 0.002). This negative correlation was consistent across subgroups and was particularly significant among women aged < 60 years, nonsmokers, and non-Hispanic Black women. However, no association was observed between serum Klotho levels and ePWV in the hypertensive group.Klotho level and ePWV in postmenopausal women. Increased serum Klotho levels may reduce arterial stiffness in postmenopausal women.Further studies are required to confirm these findings.